PERANCANGAN SISTEM INFORMASI DESA (SID) DALAM MENINGKATKAN KUALITAS PELAYANAN PUBLIK DI DESA NGAMPEL: Pengabdian Masyarakat Berbasis Teknologi Tepat Guna - Achmad Agus Athok Miftachuddin; Moh. Anshori Aris Widya; Dani Huwaidi Mushlih; Asri Sobirin (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
The limited understanding of village officials in Ngampel Village, Ngusikan District, Jombang Regency, regarding the development and utilization of the Village Information System (SID) is caused by limited human resource support and minimal facilities and infrastructure available. This condition has an impact on the low awareness of village officials regarding the importance of utilizing the village website as a tool for disseminating information. Until now, the knowledge of village officials regarding the creation and management of websites is still very limited, so that the dissemination of information through this platform has not been optimal. In this community service activity, a research team from KH. A. Wahab Hasbulloh University also designed a website for Ngampel Village and provided training to village officials to improve their ability to manage the Village Information System (SID) effectively. The main objective of this activity is to increase accessibility and socialization of village programs and information. The approach used involves the application of appropriate technology through training and management of the SID website. The results of this activity include the creation of the Village Information System (SID) website and a significant increase in the skills of village officials in managing the website.